2016
DOI: 10.1002/nau.23036
|View full text |Cite
|
Sign up to set email alerts
|

A minimum of 1‐year follow‐up for MiniArc single incision slings compared to Monarc transobturator slings: An analysis to evaluate durability of continence and medium‐term outcomes

Abstract: We demonstrated that the short-term results of MiniArc™, are maintained over time, defining the comparability of the two slings at 5 years in terms of subjective and objective outcomes and complications. Neurourol. Urodynam. 36:803-807, 2017. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
(87 reference statements)
1
7
0
Order By: Relevance
“…Additionally, the incidence of perioperative complications such as erosion was low (1.0%) in the present series. This finding is consistent with that of Tutolo et al., who also showed that low erosion was maintained over time (at 1‐, 3‐, 5‐year follow‐up endpoints) …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Additionally, the incidence of perioperative complications such as erosion was low (1.0%) in the present series. This finding is consistent with that of Tutolo et al., who also showed that low erosion was maintained over time (at 1‐, 3‐, 5‐year follow‐up endpoints) …”
Section: Discussionsupporting
confidence: 92%
“…did not report any intraoperative complications among 93 women who had sling implantation in outpatient setting. Similarly, Tutolo et al . did not find bladder perforation among 166 women undergoing the MiniArc procedure.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Twelve relevant studies [ 18 29 ] including 1794 patients were selected for analysis. No differences were found in terms of age and the basic physical conditions between the MiniArc group and transobturator MUS group.…”
Section: Methodsmentioning
confidence: 99%
“…A comparative study with a standard MiniArc midurethral sling has shown to be comparable. Tutulo et al [14] reported no apparent difference in continence rates (89% vs 87%) between the MiniArc and Monarc, with median followup of 47 months for the MiniArc and 80 months for the Monarc. The MiniArc has been noted to have a signifi-cantly shorter operating time, less blood loss, and less postoperative pain [14,15]m all of which are evident in this current study.…”
Section: Figmentioning
confidence: 96%